Galaxy Zoo: Bulgeless Galaxies With Growing Black Holes - Simmons, B; Lintott, C; Schawinski, K; Moran, E; Han, A; Kaviraj, S; Masters, K; Urry, C; Willett, K; Bamford, S; Nichol, R (2012)
The growth of supermassive black holes appears to be driven by galaxy mergers, violent merger-free processes and/or `secular' processes. In order to quantify the effects of secular evolution on black hole growth, we study a sample of active galactic nuclei (AGN) in galaxies with a calm formation history free of significant mergers, a population that heretofore has been difficult to locate. Here we present an initial sample of 13 AGN in massive (M_* >~ 1e10 M_sun) bulgeless galaxies -- which lack the classical bulges believed inevitably to result from mergers -- selected from the Sloan Digital Sky Survey using visual classifications from Galaxy Zoo. Parametric morphological fitting confirms the host galaxies lack classical bulges; any contributions from pseudobulges are very small (typically < 5%). We compute black hole masses for the two broad-line objects in the sample (4.2e6 and 1.2e7 M_sun) and place lower limits on black hole masses for the remaining sample (typically M_BH >~ 1e6 M_sun), showing that significant black hole growth must be possible in the absence of mergers or violent disk instabilities. The black hole masses are systematically higher than expected from established bulge-black hole relations. However, if the mean Eddington ratio of the systems with measured black hole masses (L/L_Edd = 0.065) is typical, 10 of 13 sources are consistent with the correlation between black hole mass and total stellar mass. That pure disk galaxies and their central black holes may be consistent with a relation derived from elliptical and bulge-dominated galaxies with very different formation histories implies the details of stellar galaxy evolution and dynamics may not be fundamental to the co-evolution of galaxies and black holes.